2008
DOI: 10.2224/sbp.2008.36.7.973
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Self-Esteem, Problem Behaviors, and Perceived Social Support in Turkey

Abstract: This study was conducted as a predictive examination of family conflict and parent and peer support on adolescent self-esteem, depression, and problem behaviors. The other aim of the study was to determine whether adolescent self-esteem, depression, and problem behaviors differed according to gender. The study sample consisted of 1,734 high school students. The results support the general hypothesis that perceptions of high conflict in the family context are related to lower levels of self-esteem and higher le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
9

Year Published

2010
2010
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 16 publications
2
14
0
9
Order By: Relevance
“…It is a result consistent with the widely accepted notion that mothers are children's closest caregivers who provide them with the most frequent interaction. This result supports Siyez's (2008) finding that parents have more influence on young adolescents' self-development than do peers. Participants in this study comprised children in their late childhood or preadolescence, so they were still in the developmental period that requires their mother's affective and responsive caregiving behavior.…”
Section: Predictors Of Susceptibility To Peer Pressuresupporting
confidence: 88%
See 1 more Smart Citation
“…It is a result consistent with the widely accepted notion that mothers are children's closest caregivers who provide them with the most frequent interaction. This result supports Siyez's (2008) finding that parents have more influence on young adolescents' self-development than do peers. Participants in this study comprised children in their late childhood or preadolescence, so they were still in the developmental period that requires their mother's affective and responsive caregiving behavior.…”
Section: Predictors Of Susceptibility To Peer Pressuresupporting
confidence: 88%
“…It has been reported that children with higher levels of peer support showed significantly higher self-esteem (Arslan, 2009;Siyez, 2008). Adolescents who receive more peer support tend to perceive themselves as worthwhile and efficacious (Liem, Cavell, & Lustig, 2010).…”
Section: Shame and Interpersonal Rejection As Predictors Of Peer Presmentioning
confidence: 99%
“…Belirtilen tüm riskli davranış türlerinde erkek öğrencilerin puanları daha yüksek bulunmuştur. Erkekler kadınlardan daha fazla riskli davranış sergilemektedir ve çeşitli çalışmalar bunu göstermektedir (Akın ve Berkem, 2012;Karahan, Sardoğan, Gençoğlu ve Yılan, 2010;Siyez, 2008;Telef, 2014). Madde kullanımının ve şiddet davranışlarının erkek öğrencilerde daha çok görülmesinde, belirtilen davranışların erkek akran grupları tarafından desteklenmesi, akran gruplarına dahil olabilme normları olarak algılanması, toplumsal cinsiyet rolleri ve toplumsal yapının desteklemesi gibi etmenlerin rol oynadığı düşünülmektedir.…”
Section: Discussionunclassified
“…4, 8, 12 ve 16. maddeleri tersten puanlanan ölçekte puan yükseldikçe depresyon semptomları da beraberinde artmış olmaktadır. Türkçeye adaptasyonu Tatar ve Saltukoğlu (2010) (Çevik, 2010;Saygın , Arslan 2009;Doğan, 2008;Yalçın, 2014;Gençöz, Özlale, 2004;Chu, Saucier & Hafner, 2010;Doğan, Sapmaz, 2012), yaşam doyumu (Yalçın, 2011), depresyon ve kaygı (Albal, 2009;Eldeleklioğlu, 2006;Paykel, 1994;Al-Issa, İsmail, 1994), yalnızlık, (Arslantaş, Ergin, 2011;Duru, 2008), psikolojik dayanıklılık (Terzi, 2008) ve öz saygı, (Siyez, 2008;Saygın vd. 2009;Kahriman, Polat 2003;Arslan, 2009) (Wallace, Bisconti, Bergeman, 2001, s. 273;Zhang, Goodson, 2011, s. 142).…”
Section: Depresyon öLçeği (Ces-d)unclassified